Profiles and treatment patterns of patients with pulmonary arterial hypertension on monotherapy at experienced centres. (15th June 2022) - Wissmüller, Max; Xanthouli, Panagiota; Benjamin, Nicola; Grünig, Ekkehard; Richter, Manuel J.; Gall, Henning; Ghofrani, Hossein Ardeschir; Herkenrath, Simon; Skowasch, Dirk; Pizarro, Carmen; Halank, Michael; Hohmann, Christopher; et al.
Abstract: Aims: Guideline recommendations highlight the critical role of combination therapy for the treatment of pulmonary arterial hypertension (PAH). Conversely, registry data demonstrate that a considerable number of PAH patients remain on monotherapy. The reasons for this discrepancy remain elusive. The aim of this study was to assess the patient profiles, treatment patterns, and disease characteristics of patients diagnosed with PAH who were kept on monotherapy at experienced pulmonary hypertension (PH) centres and to capture potential reasons for monotherapy. Methods and results: We analysed the patient profiles of 182 patients on monotherapy with PAH‐targeted drugs, managed at experienced PH expert centres (Cologne, Giessen, Heidelberg, and Dresden). Patients were identified based on their latest follow‐up visit and analysed retrospectively from the time of PAH diagnosis to last follow‐up. Patients were dichotomized by age, and patient characteristics, treatment patterns, response to therapy, change in risk status, and drug tolerability were recorded during the course of their disease. Patients' mean age was 69.1 ± 13.1 years at the most recent follow‐up (Key Time Point 1) and 64.5 ± 14.9 years at the time of diagnosis (Key Time Point 2). The mean time on monotherapy was 60.7 ± 53.8 months; 35.7/64.3% of patients were male/female. The majority (66.5%) had idiopathic PAH, followed by PAH associated with connective tissue disease (17.0%) and portopulmonary PH (8.2%). Among patients on monotherapy, there were five main clusters: (i) patients with failed escalation attempts mostly because of intolerability (26.9%); (ii) low risk on monotherapy, favourable response, and no reason for escalation (24.2%); (iii) patients with mild PAH (36.3%); (iv) elderly patients with PAH and multiple co‐morbidities (38.5%); and (v) patients with associated forms of PAH where the level of evidence for combination therapies is considered low (16.5%). There were substantial differences between patients above or below the median age (68 years). The most frequently used monotherapy for PAH was phosphodiesterase type 5 inhibitors (75.3%). Conclusions: A considerable number of PAH patients are on monotherapy at large PH expert centres, characterized by specific reasons that justify this kind of treatment. Nevertheless, as comprehensive treatment strategies have shown improved long‐term outcomes even in mildly symptomatic patients, each case of monotherapy should be justified.